Altitude ammonia-oxidizing bacteria and archaea in soils of Mount Everest - Zhang, Li-Mei; Wang, Mu; Prosser, James I; Zheng, Yuan-Ming; He, Ji-Zheng (FEMS microbiology ecology, 2009)
To determine the abundance and distribution of bacterial and archaeal ammonia oxidizers in alpine and permafrost soils, 12 soils at altitudes of 4000-6550 m above sea level (m a.s.l.) were collected from the northern slope of the Mount Everest (Tibetan Plateau), where the permanent snow line is at 5800-6000 m a.s.l. Communities were characterized by real-time PCR and clone sequencing by targeting on amoA genes, which putatively encode ammonia monooxygenase subunit A. Archaeal amoA abundance was greater than bacterial amoA abundance in lower altitude soils ([less-than or equal to]5400 m a.s.l.), but this situation was reversed in higher altitude soils (≥5700 m a.s.l.). Both archaeal and bacterial amoA abundance decreased abruptly in higher altitude soils. Communities shifted from a Nitrosospira amoA cluster 3a-dominated ammonia-oxidizing bacteria community in lower altitude soils to communities dominated by a newly designated Nitrosospira ME and cluster 2-related groups and Nitrosomonas cluster 6 in higher altitude soils. All archaeal amoA sequences fell within soil and sediment clusters, and the proportions of the major archaeal amoA clusters changed between the lower altitude and the higher altitude soils. These findings imply that the shift in the relative abundance and community structure of archaeal and bacterial ammonia oxidizers may result from selection of organisms adapted to altitude-dependent environmental factors in elevated soils.